1984
DOI: 10.1002/1097-4679(198407)40:4<1028::aid-jclp2270400427>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression in multiple sclerosis as a function of length and severity of illness, age, remissions, and perceived social support

Abstract: Degree of depression found in 120 spinal multiple sclerosis (MS) outpatients was related significantly to selected illness, demographic, and social variables. The more depressed individuals tended to be more disabled, older, and, in particular, perceived their families and friends as providing less social support than those who were less depressed. Those who had experienced at least one remission were less depressed than those who never had had a remission. Contrary to hypothesized expectations, the results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 9 publications
5
74
0
2
Order By: Relevance
“…Although a number of studies have suggested that depression, anxiety, and coping style can amplify the pain experience and increase levels of FI in other chronic diseases ( 1 1. [13][14][15], prospective longitudinal studies would be necessary to clarify more fully the potential mediating role of psychologic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have suggested that depression, anxiety, and coping style can amplify the pain experience and increase levels of FI in other chronic diseases ( 1 1. [13][14][15], prospective longitudinal studies would be necessary to clarify more fully the potential mediating role of psychologic variables.…”
Section: Discussionmentioning
confidence: 99%
“…With effective treatments widely available for several emotional disorders, this component of the burden of MS can be reduced. 1,2 Undetected and untreated mental illness may worsen functioning 3 and quality of life, [4][5][6][7][8] decrease treatment adherence, 9 and increase risk of suicide. [10][11][12][13][14][15][16] Improved detection, diagnosis, and treatment practices in medical settings where individuals with emotional disorders are often first seen would help ameliorate these negative outcomes.…”
mentioning
confidence: 99%
“…Results of the current study supported prior research in this area 20,22 in that both physical and cognitive disability (as reported by the patient) were significantly correlated with adjustment. A unique finding of this study, however, was that, in the context of all of the study variables, perceived cognitive disability (not physical disability) significantly predicted adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Because prior literature with MS patients suggests that functional disability can influence adaptation to the illness, 20,22 the current study included the Functional Independence Measure (FIM) 39 as a measure of the participants' perceived level of cognitive and physical disability. The FIM consists of 18 items, each of which is assessed on seven levels ranging from total assistance to complete independence.…”
Section: Methodsmentioning
confidence: 99%